2003
DOI: 10.1309/jd3dhgcdgaun1r0j
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Angiogenesis-Related Markers in Oral Squamous Cell Carcinomas With Multiple Metastatic Lymph Nodes

Abstract: The aim of this study was to evaluate the histopathologic features and the expression of angiogenesis-related markers in primary tumors and metastatic lymph nodes of oral squamous cell carcinomas (SCCs) with multiple lymph node involvement in comparison with oral SCCs without nodal metastasis. The protein levels of the angiogenesis inhibitor endostatin, as well as those of the related molecules collagen XVIII, collagen-binding protein (CBP) 2/heat shock protein (HSP) 47, and cathepsin L, were evaluated by immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 42 publications
6
23
1
2
Order By: Relevance
“…The comparable CB and CL immunohistochemical profiles were described in the study on oral cavity tumors by Vigneswaran et al, 23 whereas conflicting results from some other studies could have resulted from the differences in analytical procedures used (antigens, reagents), low sample numbers in some series, 24,25 and from the inherent biological characteristics of the site of tissue sampling (oral cavity vs. oropharynx vs. other tumor types). 6,7,27 The observed perinuclear cathepsin positivity mainly manifested intracellularly and on the membrane surface outside the tumor cells, was more consistent throughout the studies (Figure 5a).…”
Section: Immunohistochemistrymentioning
confidence: 79%
See 2 more Smart Citations
“…The comparable CB and CL immunohistochemical profiles were described in the study on oral cavity tumors by Vigneswaran et al, 23 whereas conflicting results from some other studies could have resulted from the differences in analytical procedures used (antigens, reagents), low sample numbers in some series, 24,25 and from the inherent biological characteristics of the site of tissue sampling (oral cavity vs. oropharynx vs. other tumor types). 6,7,27 The observed perinuclear cathepsin positivity mainly manifested intracellularly and on the membrane surface outside the tumor cells, was more consistent throughout the studies (Figure 5a).…”
Section: Immunohistochemistrymentioning
confidence: 79%
“…[23][24][25][26] So far, to the best of our knowledge, stefins have not been subjected to immunohistochemical evaluation in any of the studies conducted on head and neck carcinomas. The results on spatial distribution of CB and CL immunoreactivity, with perinuclear positivity mainly manifested intracellularly and on the membrane surface outside the tumor cells, reflect their physiological role and are consistent throughout the studies.…”
Section: What Do We Know?mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, higher collagen XVIII in tumor was found to be associated with worse prognosis in several malignancies (34). However, there were contradictory results (35,36). No correlation was found between endostatin expression in tumor tissue and NSCLC patient prognosis in a study from Korea, which was confirmed by our observation (37).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, these results contradict with those of Homer et al (Homer, et al, 2002), who observed a positive trend between higher levels of endostatin and nodal metastasis and an association between increased endostatin expression and higher tumor grade, recurrence, and death in patients with HNSCC. The authors attributed this discrepancy to differences in methods used, as these investigators measured the circulating levels of endostatin, whereas this study assessed the levels in tissue samples (Nikitakis, et al, 2003).…”
Section: Endostatinmentioning
confidence: 99%